2018
DOI: 10.1007/s10816-018-9384-0
|View full text |Cite
|
Sign up to set email alerts
|

Pastoralist Foodways Recorded in Organic Residues from Pottery Vessels of Modern Communities in Samburu, Kenya

Abstract: Organic residue analyses of archaeological ceramics can provide important insights into ancient foodways. To date, however, there has been little critical reflection on how lipid residues might (or might not) reflect dietary practices or subsistence strategies more generally. A combination of ethnoarchaeological research and chemical and isotopic analyses of lipid residues from pottery made and used by modern Samburu pastoralists in northern Kenya was undertaken to supplement the interpretive framework used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 72 publications
(85 reference statements)
1
32
0
Order By: Relevance
“…These differences can, therefore, be crudely described as sub-regional 'cuisines'. From an anthropological perspective, this observation is perhaps of no surprise, as all documented hunter-gatherers practice some form of culturally specific custom for food preparation and consumption, often deploying specific material culture for defined tasks [107][108][109]. Whether such 'culinary traits' can be used to help understand the dispersal dynamics of pottery technology is debatable.…”
Section: Resultsmentioning
confidence: 99%
“…These differences can, therefore, be crudely described as sub-regional 'cuisines'. From an anthropological perspective, this observation is perhaps of no surprise, as all documented hunter-gatherers practice some form of culturally specific custom for food preparation and consumption, often deploying specific material culture for defined tasks [107][108][109]. Whether such 'culinary traits' can be used to help understand the dispersal dynamics of pottery technology is debatable.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the use-alteration analysis of the pottery and the faunal analysis suggest that Mota Cave inhabitants had culinary practices that differed from those inhabiting Tuwatey Cave (Table 18). Usealteration analysis is beginning to be more widely utilized in African archaeology (e.g., Arthur 2002Arthur , 2003Arthur , 2014Dunne et al 2012Dunne et al , 2018Reid and Young 2000). Ethnoarchaeological studies of ceramic use have confirmed specific use-alteration patterns, such as carbon deposits and surface abrasions on ceramic vessels that represent specific types of food processing (e.g., Arthur 2014; Skibo 1992Skibo , 2013.…”
Section: Historic Period (500-120 Bp)mentioning
confidence: 99%
“…Lipid residues demonstrate that herders at the Luxmanda and Ngamuriak settlement sites used their pottery predominantly for processing ruminant carcass products, and to a lesser extent for processing milk. Comparison with lipid residues extracted from ceramics used by heavily milk-reliant Samburu pastoralists in northern Kenya today revealed a broadly similar pattern (38). In Samburu, this pattern reflects container choices, rather than degree of reliance on milk in the diet (9).…”
Section: Discussionmentioning
confidence: 92%